Feasibility of wavelength dispersive X-ray fluorescence spectrometryfor the determination of metal impurities in pharmaceutical productsand dietary supplements in view of regulatory guidelines - Figueiredo, Alexandra; Fernandes, Tânia; Costa, Isabel Margarida; Gonçalves, Luísa; Brito, José (Elsevier, 2016)
The aim of this study was to investigate the feasibility of Wavelength Dispersive X-ray Fluorescence (WDXRF) spectrometry for the measurement of As, Cd, Cr, Cu, Hg, Ir, Mn, Mo, Ni, Os, Pb, Pd, Pt, Rh, Ru and V impurities in pharmaceuticals and dietary supplements, in view of the requirements by EMA and USP for the measurement of elemental impurities in drug products and according to the International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH guidelines). For that purpose, a 4 kW WDXRF spectrometer (S4 Pioneer, Bruker AXS) was used after system calibration. The linearity of the method was demonstrated by correlation coefficients in excess of 0.9 and by appropriate test of lack of fit, except for Cd, Hg, Pd, V and As, which were excluded from analysis. The calculated limits of detection and quantification were in the ranges 0.6-5.4 μg/g and 1.7-16.4 μg/g meeting defined acceptance criteria, except for Pb. The accuracy of the method, determined by the percent recovery (R) of known amounts of each element added to a selected drug, at 3 different concentration levels, was in the acceptance range 70-150% except for Os and Pt, in which case R was marginally outside that range. The repeatability of the method, assessed as the % residual standard deviation (%RSD) of 3 replicate measurements at 3 concentration levels, produced %RSD values lower than 20%, as required. These results show that the WDXRF method complies with the validation requirements defined by the European Pharmacopeia for Cu, Cr, Ir, Mn, Mo, Ni, Os, and Pt, and by the United States Pharmacopeia for Ir, Ni, Os and Pt. Therefore, it may be an alternative to the compendial analytical procedures recommended for such elements. The novelty of the present work is the application of WDXRF to final medicines and not only to active pharmaceutical ingredients and/or excipients.
Keywords: Metal impurities; X-ray Fluorescence; Validation; Pharmaceutical products; Dietary supplements